Mindfulness-Based Stress Reduction (MBSR) as a Standalone Intervention for Posttraumatic Stress Disorder after Mixed Traumatic Events: A Mixed-Methods Feasibility Study - Müller-Engelmann, Meike; Wünsch, Susanne; Volk, Marina; Steil, Regina (Frontiers in Psychology, 2017)
Objectives: There is promising evidence that mindfulness-based interventions are effective in reducing the symptoms of posttraumatic stress disorder (PTSD). However, until now, studies have often lacked a full clinical PTSD assessment, and interventions are often administered in addition to other interventions. This study examined the feasibility of mindfulness-based stress reduction (MBSR) as a standalone intervention in patients with PTSD who have experienced mixed traumatic events. Method: Fourteen patients participated in 8 weeks of MBSR. The patients were assessed prior to treatment, post-treatment and at a 1-month follow-up through self-ratings (e.g., the Davidson Trauma Scale) and the Clinician-Administered PTSD Scale to determine the effects of the intervention. Furthermore, after the intervention, the patients participated in qualitative interviews regarding their experiences with MBSR and their ideas for future improvements. Results: Nine patients finished the program, and these patients considered the exercises to be applicable and helpful. In the Clinician-Administered PTSD Scale, we found large effects regarding the reduction of PTSD symptoms among completers (Cohen's d = 1.2). In the Davidson Trauma Scale, the effect sizes were somewhat lower (Cohen's d = 0.6) but nevertheless confirmed the efficacy of MBSR in reducing PTSD symptoms. In the qualitative interviews, the patients reported an augmentation of wellbeing and improvement regarding the handling of difficult situations and more distance from the traumatic event. Conclusion: Despite the large effects, the high dropout rates and the results of the post-treatment interviews suggest that the intervention should be better adapted to the needs of PTSD patients, e.g., by giving more information regarding the exercises and by including shorter exercises to manage acute distress.